Juvenile idiopathic arthritis in Jordan: single center experience - Raed M. Alzyoud; Motasem O. Alsuweiti; Heba Q. Almaaitah; Bushra N. Aladaileh; Mohammad K. Alnoubani; Adel M. Alwahadneh (BMC, 2021)
Abstract Background Juvenile idiopathic arthritis (JIA) is a heterogeneous group of disorders, including all forms of arthritis, which develops in children who are less than 16 years old. This study aimed to evaluate the clinical and laboratory features of JIA in a single center in Jordan. Methods A retrospective analysis of the electronic medical records of Pediatric patients diagnosed with JIA based on the International League of Associations for Rheumatology (ILAR) criteria during the period from 2015 to 2019 at the Pediatric Rheumatology Clinic in the Queen Rania Children's Hospital. All patients were below the age of 14 years at the time of diagnosis and followed for at least 6 months. Collected data consisted of age, gender, age at initial presentation and diagnosis, JIA subtype, laboratory data, treatment options, and outcome. Results A total of 210 patients were included in this cohort (94 males and 116 females) with the mean age at diagnosis and mean age at onset of 5.33 ± 3.40 years and 5.08 ± 3.40 years (range: 7 months - 14 years), respectively. Oligoarticular JIA was the commonest subtype (54.7%), followed by systemic arthritis (17.1%) and polyarticular arthritis (12.3%). ANA was positive in 70 patients (33.6%). Uveitis occurred in 30 (14.2%) patients. Conclusion To the best of our knowledge, this study on this cohort is the first report on JIA in Jordan, in comparison with other regionally and internationally published reports. Oligoarticular JIA was found to be the most common subtype. For detailed knowledge on JIA characteristics and patterns, a population-based, rather than a single center study, should be conducted in Jordan.